Recent progress in chemical vapor deposition growth of two-dimensional transition metal dichalcogenides. Issue 3 (September 2016) - Wong, Swee Liang; Liu, Hongfei; Chi, Dongzhi
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDCs) have received significant attention recently due to their unique properties such as a transition from indirect to direct band gap when thinned down to a monolayer and also valley-dependent photoluminescence. In addition, being a semiconductor with considerable mobility, it has been touted as a candidate in next generation electronics. However, a major hurdle to its implementation is the difficulty in producing large areas of these 2D TMDCs with well-defined thicknesses. In this review, we will first introduce the basic properties as well as the various synthesis methods of 2D TMDCs. Focus will be placed on recent advances in chemical vapor deposition (CVD) growth as they currently yield the largest areas. Obstacles present in CVD growth will be presented and existing solutions to them will be discussed in tandem with current characterization methods for evaluation of crystal quality. Through our presentation on the latest approaches to issues in CVD growth, we hope to present the readers a perspective on recent developments as well as providing an outlook on the future of CVD growth of TMDCs.